Effects of infectious bursal disease virus and cyclophosphamide on immune response against Newcastle disease vaccination in broiler chicks - MAYAHI, MANSOOR; B FARD, M H (The Indian Journal of Animal Sciences, 2013)
A study conducted on day-old broiler chicks to determine the effect of infectious bursal disease (IBD) infection and cyclophosphamide (CV) administration on the immune response to Newcastle disease (ND) vaccination revealed that IBD infection had an immunosuppressive effect on ND vaccination; and that this effect was more pronounced when the IBD infection occurred in early age. The immunosuppression waS less marked against revaccination with ND vaccine. The administration of CY also had similar immunosuppressive effect, but the effect was nonpersistent and valid only for the initial vaccination with ND vaccine.